EMPOWERING YOUTH: PROMOTING SUBJECTIVE WELL-BEING AMONG THAI ADOLESCENTS OF LOW SOCIOECONOMIC STATUS THROUGH POSITIVE PSYCHOLOGY INTERVENTION - Lamprasitipon, Permsit; Blauw, Jon (Scholar: Human Sciences, 2018)
This quiz-experimental study examined the effectiveness of a 10-hour workshop-based intervention program that incorporated positive psychology strategies. Participants in the study included 72 Thai adolescents age 14 to 17 years with low socioeconomic status from four Fai-Fah centers, two of which were randomly assigned to one of two experimental conditions: (1) the Positive Empowerment for Adolescents (PEA) group or (2) the expressive writing and reading control group. PEA is a series of positive psychology interventions including character strength enhancement, goal setting, problem solving skills, and gratitude journaling and letter writing. Data were collected on participants at pre-and-post intervention including self-report measures of life satisfaction, positive affect ratio, self-efficacy, and perceived social support, by using Brief Multidimensional Students’ Life Satisfaction Scale (BMLSS), Positive and Negative Affect Schedule for Children (PANAS-C), Self-Efficacy Questionnaire for Children (SEQ-C), and Child and Adolescent Social Support Scale (CASSS) respectively. The results suggested that the PEA intervention program had a significant effect on the level of self-efficacy and perceived social support, although there were no significant effects on positive affect ratio. Surprisingly, the control group subjects showed a significantly higher level of life satisfaction than the experimental group. Integration of the expressive writing and reading found to be effective at raising life satisfaction from the control group, as well as elements of traditional Thai cultural practices such as meditation are recommended to help strengthen the PEA intervention program.